2021
DOI: 10.21037/jtd.2020.04.13
|View full text |Cite
|
Sign up to set email alerts
|

US women in thoracic surgery: reflections on the past and opportunities for the future

Abstract: Historical perspective of women in thoracic surgeryThe history of women surgeons spans more than 5,500 years. According to the Iliad, in Ancient Greece, women performed various surgical techniques, attended births, and treated the wounds of warriors (1). In modern times, after formal medical schools were established in the United States (US), women initially were excluded from studying medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Sponsorship entails being an advocate for an individual, opening doors to further success, and leadership. 6 In our survey, 66.7% of women (18/27) have never had a female sponsor or a woman who has written a letter of recommendation, whereas only 33.33% (9/27) have. Efforts have been made by several organizations toward promotion and sponsorship.…”
Section: Sponsorship/promotionmentioning
confidence: 66%
See 3 more Smart Citations
“…Sponsorship entails being an advocate for an individual, opening doors to further success, and leadership. 6 In our survey, 66.7% of women (18/27) have never had a female sponsor or a woman who has written a letter of recommendation, whereas only 33.33% (9/27) have. Efforts have been made by several organizations toward promotion and sponsorship.…”
Section: Sponsorship/promotionmentioning
confidence: 66%
“…Dr Barry concealed her sex throughout the duration of her practice and was found to be female after her death in 1865. 6 The American College of Surgeons admitted its first female member in 1913 and 5 or fewer women each year thereafter, until 1975. 4 Even in the advent of modern surgical training, brought by Halstead, this road has proven difficult for women.…”
Section: Historical Perspectivementioning
confidence: 99%
See 2 more Smart Citations
“…Cardiac surgery has even fewer female surgeons than neurosurgery. For example, a 2010 survey of American surgeons found that women made up only 3.4% of adult cardiac, 5.2% of congenital heart, and 7.9% of general thoracic surgeons (Preventza & Backhus, 2021). As with neurosurgery, female cardiac surgeons are underrepresented in academic leadership positions and senior-level authorship publications (Preventza & Backhus, 2021).…”
Section: Women In Cardiac Surgerymentioning
confidence: 99%